Anatomy of the maxillary sinus: implications for odontogenic sinusitis development - Gorbik, E. V.; Ohurtsov, O. S.; Heranin, S. I.; Kolba, O. O.; Breslavets, N. M.; Sazonova, O. M.; Sazonova, O.M.; Kysylenko, K. V.; Alekseeva, V. V. (Tbilisi : Nʹi︠u︡-Ĭork : Assot︠s︡iat︠s︡ii︠a︡ delovoĭ pressy Gruzii ; International Academy of Science, Education, Industry & Arts, 2024)
This study investigates the anatomical prerequisites that could contribute to the development of this condition. Material and methods: Using multi-slice computed tomography (MSCT), the study examined the structure and relationships of key anatomical features, including the alveolar process, sinus wall thickness, and the position of the teeth in relation to the maxillary sinus. Results: The results revealed that the lower wall of the maxillary sinus is predominantly formed by the alveolar process, with significant variability in wall thickness, especially between the central and lateral regions. In 95% of cases, this wall was closely associated with the roots of the upper teeth, particularly the premolars. A strong negative correlation was observed between the thickness of the alveolar process and the volume of the maxillary sinus, suggesting that larger sinuses tend to have thinner alveolar processes. Additionally, a significant correlation was found between the position of the sinus and the degree of pneumatization, with a more medially positioned orbit in cases of reduced pneumatization. Conclusion: Structural features of the maxillary sinus, such as its proximity to the teeth and its relationship to sinus pneumatization, are critical factors in the development of odontogenic rhinosinusitis. A comprehensive, collaborative approach is necessary for effective management and prevention, with careful consideration of these anatomical aspects during dental and maxillofacial interventions.
Funding: This research received no external funding. Conflict of interest statement: The authors declare that the research was conducted in the absence of any commercial or financial relationships that could be construed as a potential conflict of interest.
Keywords: MEDICINE; maxillary sinus; MSCT; odontogenic sinusitis; anatomical predispositions